METAPHORICAL ASSOCIATIVE CARDS IN THE SITUATION OF CHOICE - USM ADMIN (Moldova State University, 2018)
In this paper, we propose to review the possibility of metaphorical associative cards using in the situations of choice. The value of choice, its role in the formation of the essential person's characteristics is the topic of non-classical humanistic-oriented psychological theories and concepts. Working with time line allows modeling and investigating any processes in the past and future, finding solutions with cards metaphorical images, creating for the client a special reality, which can be subsequently embodied in his life. Keywords: metaphorical associative cards, situations of choice, solution, psychological councelling.